The relationship between physical fitness and academic achievement in middle school students in Shanghai - Xu, Y (2021)
The relationship between physical fitness and academic achievement in relation to children and adolescents has received attention from an increasing number of researchers in various fields across the world. Large bodies of literature based on insights from neuroscience have reported a positive relationship between the overall or some specific components of physical fitness and academic achievement in different educational contexts. Furthermore, many neuroscientists have revealed that the mind and body are connected through the mechanisms of neurochemistry. It has been found that performing physical exercise can optimise the brain’s cognitive functions by stimulating brain-derived neurotrophic factor (BDNF) release, thus contributing to brain development. Physical exercise can also increase the level of neurotransmitters such as dopamine, serotonin and noradrenaline, which can improve concentration and positive emotional states for learning. However, the research findings are still under debate due to inconsistencies between studies conducted in school settings, where the results are more likely to be influenced by various confounding factors.